Single-Session Attention Bias Modification Training in Victims of Work-Related Accidents - Buodo, Giulia; Patron, Elisabetta; Messerotti Benvenuti, Simone; Palomba, Daniela (Frontiers in Psychology, 2018)
Individuals who experienced traumatic work-related accidents frequently show cognitive deficits and biased processing of trauma-relevant information, which, in turn, could increase the risk of further accidents. The Attention Bias Modification Training (ABMT) is designed to reduce hypervigilance toward and enhance attentional disengagement from threat stimuli. The aim of the present study was to assess whether it is possible to implicitly reduce the attentional bias toward trauma-related stimuli through a single session of ABMT in individuals who experienced a traumatic occupational accident. Nineteen individuals who had experienced a traumatic work-related accident and 11 workers who never experienced a work accident (control group) underwent a preliminary assessment of cognitive performance (executive functions and sustained attention) and an evaluation of the attentional bias toward accident-related pictures by means of a dot-probe task. The results showed that injured workers performed more poorly than controls in tasks of executive functions and concentration abilities. Also, injured workers showed an attentional bias toward trauma reminders (i.e., faster reaction times [RTs] to probes replacing trauma-related pictures). Injured workers were then randomly allocated to a single-session of ABMT (N = 10) or to an Attention Control Condition (ACC; N = 9). After the training, the dot-probe task was administered again to assess changes in the attentional bias toward trauma-relevant pictures. Injured workers who underwent the ABMT, but not those who underwent the ACC, showed a significant reduction of the attentional bias from pre- to post-training. Overall, these results support previous findings reporting an association between traumatic occupational accidents and cognitive dysfunctions. More importantly, these preliminary findings add to a growing body of evidence suggesting the effectiveness of a short ABMT in reducing the attentional bias after a traumatic workplace accident.